GIS-based reservoir planning with limited data in developing nations: a case study of the Lower Mekong River Basin - Cvar, Aaron, author; Grigg, Neil S., advisor; Labadie, John, committee member; Fontane, Darrell, committee member; Leisz, Stephen, committee member; Laituri, Melinda, committee member (Colorado State University. Libraries, 2014)
To view the abstract, please see the full text of the document.
Keywords: decision support; water resources; GIS; geographic information systems